Papieren Hollanders. Werken met behoud van het Nederlandschap in 1892–1914 - Salemink, Theo (Van huis en haard. Migratie door de eeuwen heen, 2023)
Keywords: Achterhoek (Landschaft); Bocholt; Gendringen; Grenzarbeitnehmer

Unternehmer mit niederländischen Wurzeln und niederländische Arbeiter auf der westmünsterländischen Seite der Baumwollstraße um 1900 - Freitag, Werner (Westfälische Forschungen, 2020)
Keywords: Ausländischer Arbeitnehmer; Grenzarbeitnehmer; Grenzgebiet; Münsterland (West); Niederländer; Textilindustrie; Unternehmen

Salmische Hatschierer attackieren einen niederländischen Juden in Stadtlohn. Ein Prozess in Vreden im Jahre 1803 - Aschoff, Diethard (Zur Geschichte des Westmünsterlandes, Band 2. Sandstein, Hatschierer, Seidenbau und Kurzbiographien, 2013)
Keywords: Gendarmerie; Gewalt; Grenzarbeitnehmer; Juden; Münsterland (West); Prozess; Stadtlohn; Vreden

Werken over de grens - Smit, Jan (Gelderland. 1900–2000, 2006)
Keywords: Grenzarbeitnehmer

Spheres of Transnationalism within the European Union. On Open Doors, Thresholds and Drawbridges along the Dutch–German Border - Strüver, Anke (Journal of Ethnic and Migration Studies, 2005)
Abstract: „This article addresses the European Union's claim to establish transnational spaces through co-operation across its internal borders. Focusing on the Dutch–German borderland as an example, people's practices towards this border and their perceptions of it are introduced. It is underscored that these practices are influenced by popular representations, which (re)produce bounded spaces and the barrier effect of the border, thus making it difficult to imagine a transnational space. This observation is complemented by the phenomenon that—due to a housing shortage in the Netherlands—Dutch people have recently begun to move to German places directly on the border, although they maintain their jobs in the Netherlands. Concentrating specifically on one of these German villages, Kranenburg, the emergence of a community of transmigrants is highlighted in order to reflect upon the question of whether this form of frequent short-distance border crossing fosters a European transnational sphere.“
Keywords: Europäische Integration; Grenzarbeitnehmer; Grenzgebiet; Kranenburg (Kleve); Sozialraum; Transnationalisierung